Synthesis and Biological Evaluation of Thio-Derivatives of 2-Hydroxy-1,4-Naphthoquinone (Lawsone) as Novel Antiplatelet Agents - Monroy-Cárdenas, Matías; Méndez, Diego; Trostchansky, Andrés; Martínez-Cifuentes, Maximiliano; Araya-Maturana, Ramiro; Fuentes, Eduardo (Frontiers in Chemistry, 2020)
We designed and synthesized on the water by conventional heating and microwave irradiation, new thio-derivatives of 2-hydroxy-1,4-naphthoquinone, a naturally occurring pigment known as lawsone or hennotannic acid, improving their antiplatelet activity with relevance to their potential future use in thrombus formation treatment. The structure-activity relationship showed that the thiophenyl moiety enhances the antiplatelet activity. Moreover, the position and nature of the substituent at the phenyl ring have a key effect on the observed biological activity. Compound 4 (2-((4-bromophenyl)thio)-3-hydroxynaphthalene-1,4-dione) was the most active derivative, presenting IC50 values for platelet aggregation inhibition of 15.03±1.52 μM for TRAP-6, and 5.58±1.01 μM for collagen. Importantly, no cytotoxicity was observed. Finally, we discussed the structure-activity relationships of these new lawsone thio-derivatives on inhibition of TRAP-6- and collagen-induced platelet aggregation.